Al-Qur'an educational garden at Al-Amin Mosque padukuhan nangsri kidul, candirejo sub-district - Iswanto Suwarno; Robbi Rahim; Mohammad Aljanabi; Omar Tanane; Erwin L. Rimban; Manvender Kaur Sarjit Singh (Peneliti Teknologi Teknik Indonesia, 2022)
TPA activities at the Al-Amin mosque had been inactive for a while, therefore the KKN team wanted to revive TPA activities in the Nangsri Kidul hamlet. Parents in Nangsri Kidul welcomed our intention, so our group immediately discussed the continuation of TPA activities with the RT and Karang Taruna members who were in charge of TPA activities. Until finally the TPA schedule is determined. TPA activities are held twice a week. The TPA activities were attended by children from the early childhood, elementary, to junior high school levels. The activities carried out were in the form of guidance on reading Iqro'. In addition, other interlude activities are often held so that children are more interested in participating in TPA, such as exchanging gifts, drawing, coloring and writing hijaiyah letters.